A nitrogen-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:I thin film material and preparation method thereof

By introducing nitrogen and iodine co-doping into the dilute magnetic semiconductor (Zn90%, Cr10%) Te material, and using molecular beam epitaxial technology and low-temperature annealing treatment, the problem of lattice defects in the material's application restricted and doping process at room temperature is solved, and the combination of ferromagnetic and semiconductor characteristics and high-quality growth of the material is achieved.

CN115171996BActive Publication Date: 2025-04-11CHENGDU HIWAFER SEMICON CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210771227.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-30
Publication Date
2025-04-11
Estimated Expiration
2042-06-30

AI Technical Summary

Technical Problem

The existing dilute magnetic semiconductor materials are limited in their application at room temperature, and lattice defects and metastable decomposition are easily formed during doping, affecting the semiconductor characteristics of the material.

Method used

By introducing nitrogen and iodine co-doping into the dilute magnetic semiconductor (Zn90%, Cr10%) Te material, the number of electrons in the Cr 3d orbital is changed, the probability of metastable decomposition of Cr atoms is reduced, and the crystallization quality of the material is improved through molecular beam epitaxial technology and low-temperature annealing treatment.

Benefits of technology

A dilute magnetic semiconductor thin film that maintains ferromagnetic and semiconductor characteristics at room temperature is realized, reducing the probability of forming CrTe hexagonal unit cells, and improving the crystallization quality of the material and the prospect of industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115171996B_ABST
    Figure CN115171996B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of rare earth magnetic semiconductor films, and in particular to a nitrogen-containing rare earth magnetic semiconductor (Zn 90% ,Cr 10% ) Preparation method of Te:I thin film material. The content of Cr atoms in the thin film material is 10%. By doping iodine and nitrogen elements, the carrier concentration can reach 10 19 cm ‑3 In addition, the binding energy between Cr atoms is increased after N doping, so that the Cr atoms are evenly distributed in the film due to repulsion. In addition, the probability of metastable decomposition of Cr in the film can be further reduced by low-temperature annealing. The nitrogen-diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:I thin film has both ferromagnetic and semiconductor properties, and the Curie transition temperature of ferromagnetism can reach 300K at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of n-type diluted magnetic semiconductors, and in particular to a nitrogen-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:I thin film material and preparation method thereof. Background Art

[0002] With the development of processing technology for semiconductor integrated circuits, the minimum line width of transistors has been reduced to 5nm, the size of devices has become smaller and smaller, the number of transistors per unit area has also increased significantly, and the relative power consumption has also increased. However, semiconductors based on Si-based materials are constrained by the physical limits of the materials themselves and cannot further reduce the characteristic line width. In the 1960s, many researchers, in the process of studying electron spin and semiconductor properties, believed through theoretical calculations that the spin state of the electron itself and the movement state of the electron can be controlled at the same time. The direction of the electron spin can be controlled by external magnetism, and the on and off of the electron in the circuit can be controlled by external voltage, so as to realize the transmission and operation of "0" and "1" information. Therefore, the concept of Diluted Magnetic Semiconductors (DMS) was proposed.

[0003] Semiconductors formed by replacing some atoms in semiconductors with transition zone elements, such as Mn, Co, Fe, Cr, etc., or rare earth elements such as Nd and Pr, are called rare magnetic semiconductors. The material exhibits magnetism under the interaction between the electrons in the d orbit of the transition zone elements and the free carrier p orbit electrons in the semiconductor, as well as the double exchange interaction, and the material also has the characteristics of a semiconductor. Rare magnetic semiconductor materials can be used to make electronic spin transistors, etc. Among them, most of the research is based on III-V and II-VI compound semiconductors.

[0004] Among the many DMS material studies, (Ga, Mn) As has attracted much attention. This material has ferromagnetic and semiconductor properties, and the theoretical value of the ferromagnetic Curie temperature is as high as 120K. If this material needs to be applied, it is necessary to specially design a low-temperature environment required for the normal operation of electronic devices, which greatly increases the processing cost and cannot be applied on a large scale. With the development of research, the ferromagnetic Curie temperature of (Zn, Cr) Te material calculated by theory is as high as 300K at room temperature. Therefore, devices made of (Zn, Cr) Te material are expected to work at room temperature. In addition, (Zn, Cr) Te material itself is a semiconductor material, and carriers cannot move freely in the material. It is necessary to dope (Zn, Cr) Te to obtain p-type and n-type (Zn, Cr) Te semiconductors.

[0005] In order to obtain n-type (Zn, Cr) Te semiconductor, the donor impurity elements include Cl, Al, I and other elements. There are two doping methods: MBE method and MOCVD growth method. Whether the MBE method or MOCVD growth method is used, during the heating growth of the metal / metal compound, various elements will form Zn-Zn bonding, Te-Te bonding, bonding between donor impurities, etc. due to the problem of covalent binding energy during thermal equilibrium, thereby causing the local area of ​​the semiconductor material to lose the characteristics of the semiconductor itself and show the characteristics of the metal. In addition, when Al or I, Cl elements are doped into (Zn, Cr) Te as donor impurities, special consideration should be given to the heat energy exchange between Al and Zn, I / Cl and Te elements, otherwise it is easy to form lattice defects, so that Al, I, Cl form deep energy levels in the semiconductor, causing deformation of the semiconductor energy level, resulting in a decrease in the performance of the device made based on this material.

[0006] Kuroda et al. (Ozaki N, Nishizawa N, Marcet S, et al. Significant Enhancement of Ferromagnetism in Zn 1-x Cr x Te Doped with Iodine as an n-Type Dopant[J].Physical Review Letters,2006.) The (Zn,Cr)Te:I material with a Cr content of 5% was produced by MBE. The film material has both ferromagnetic and semiconductor properties, and the Curie temperature can reach 300K at room temperature. However, further research shows that metastable decomposition occurs in the film material. This is because the binding energy between Cr atoms and the nearest neighboring Cr atoms is negative, so the Cr atoms are affected by gravity, resulting in the formation of a Cr-enriched area of ​​tens of nanometers in size in the film. In this area, Cr and Te atoms form a CrTe structure. The CrTe structure is a hexagonal unit cell structure, which will deteriorate the ZnTe sphalerite structure. In addition, CrTe is a semi-metallic material that will destroy the semiconductor properties of ZnTe, such as changing the band structure of ZnTe. Summary of the invention

[0007] In view of the above problems, the present invention provides a nitrogen-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:I thin film material and a method for preparing the material.

[0008] The inventors found that in nitrogen-containing diluted magnetic semiconductors (Zn 90% ,Cr 10% )In the Te:I film, the material will exhibit ferromagnetic properties only when the distance between Cr atoms is in an appropriate range.

[0009] The n-type semiconductor material of the present invention changes the number of electrons in the Cr 3d orbital by co-doping nitrogen and iodine into a rare-earth magnetic semiconductor film, thereby reducing the probability of metastable decomposition of Cr atoms, making the distance between Cr atoms farther, and reducing the probability of forming a Cr-Cr metal body, while not changing the ferromagnetic Curie temperature of the material.

[0010] The present invention aims to provide a nitrogen-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% ) The preparation method of Te:I thin film material is as follows:

[0011] Step 1: Pre-growth treatment of the semi-insulating GaAs substrate

[0012] As in the surface atomic layers of the GaAs substrate reacts chemically with oxygen in the air to form an As oxide film with a thickness of several nm. In addition, during transportation and unsealing, organic particles floating in the air adhere to the surface of the GaAs substrate under the action of gravity and electrostatic force. These oxides, organic or inorganic particle pollutants can seriously affect the properties of the semiconductor, such as destroying the high resistance state of the substrate. Therefore, it is necessary to treat these substances. The present invention uses sulfuric acid: hydrochloric acid: hydrogen peroxide to soak and clean the GaAs substrate, and stirs it at the same time. The soaking and stirring cleaning time is 5 minutes. Finally, 99% anhydrous ethanol is used for cleaning and dehydration.

[0013] Furthermore, the volume ratio of sulfuric acid:hydrochloric acid:hydrogen peroxide is 4:1:1.

[0014] Step 2: Treating GaAs surface defects using molecular beam epitaxy

[0015] After pre-treatment, oxides are still present on the surface of the GaAs substrate, and damage and lattice defects are inevitably present on the surface of the GaAs substrate.

[0016] For the oxide on the surface of the substrate, the present invention removes the oxide film on the surface by heating the temperature to 500-600°C and maintaining it for 4-6 minutes. The oxide can be completely evaporated from the surface of the substrate within this time and temperature range, achieving the removal effect.

[0017] In a specific embodiment of the present invention, when removing the oxide film on the surface, the temperature is raised to 560° C. and maintained for 5 minutes.

[0018] When the GaAs substrate is heated up, especially when the temperature exceeds 400°C, As atoms will evaporate from the surface, causing lattice defects on the substrate surface. At this time, As atoms need to be compensated.

[0019] In view of the lattice defects on the substrate surface, the present invention uses molecular beam epitaxy technology to compensate As atoms. The compensation method is to evaporate Te atoms, Se atoms, and As atoms onto the substrate surface, including but not limited to, so as to achieve the purpose of lattice defect repair.

[0020] In a specific embodiment of the present invention, a Te atom source is used to compensate As atoms. If As atoms are used for compensation, within this temperature range, Ga and As atoms from the As evaporation source will undergo secondary decomposition after combining. However, the binding energy of Ga-Te is greater than that of Ga-As, which reduces the probability of secondary decomposition after combining, so it is preferred that Te atoms compensate the substrate surface.

[0021] In a specific embodiment of the present invention, the molecular line intensity of Te atoms is 5x10 -8 Torr.

[0022] Through the above steps, the organic or inorganic pollutants on the substrate are thoroughly cleaned, thereby ensuring the high resistance state of the GaAs substrate.

[0023] "Molecular beam epitaxy" is a new technology for growing high-quality crystal films on crystal substrates. Under ultra-high vacuum conditions, the vapor generated by heating a furnace filled with various required components is collimated by a small hole to form a molecular beam or atomic beam, which is directly sprayed onto a single crystal substrate at an appropriate temperature. At the same time, the molecular beam is controlled to scan the substrate, so that molecules or atoms can be "grown" layer by layer on the substrate according to the crystal arrangement to form a thin film.

[0024] Step 3: Growth of ZnTe buffer layer

[0025] The lattice constant of GaAs is Nitrogen (Zn 90% ,Cr 10% )The lattice constant of Te:I film is There is a 7% mismatch in the lattice constant. 90% ,Cr 10% )Te:I thin film, a ZnTe buffer layer needs to be grown on the GaAs substrate.

[0026] In the technical solution of the present invention, the specific method of growing the ZnTe buffer layer (Buffer) is as follows: when the growth temperature is in the range of 280-320°C, Zn atoms and Te atoms can form a ZnTe compound semiconductor. At temperatures outside the range of 280-320°C, Zn-Zn regions and Te-Te regions will be formed, showing metallic properties. The optimal growth temperature of the present invention is 300°C. Under this temperature condition, the molecular line intensity ratio of Zn / Te is adjusted to 1:1.5. After the film is grown for 1 hour, the lattice constant of the ZnTe buffer layer can reach The lattice constant of the (Zn,Cr)Te:I film is close to that of the ZnTe layer, thus ensuring that the nitrogen-containing (Zn 90% ,Cr 10% )High-quality growth of Te:I thin films.

[0027] Wherein, the thickness of the ZnTe buffer layer is 50-400 nm.

[0028] Furthermore, the growth thickness of the ZnTe buffer layer is 50-360 nm.

[0029] Furthermore, the growth thickness of the ZnTe buffer layer is 360 nm.

[0030] Step 4: Nitrogen (Zn 90% ,Cr 10% ) Growth of Te:I thin film

[0031] In the present invention, nitrogen (Zn 90% ,Cr 10% )When the Te:I thin film layer grows, the molecular line intensity ratio of Zn / Te is 1.2~1.8:1 in the MBE growth chamber.

[0032] Furthermore, in the technical solution of the present invention, the molecular line intensity ratio of Zn / Te is 1.5:1.

[0033] Furthermore, in the technical solution of the present invention, the total molecular line intensity of Zn atoms and Te atoms is 8x10 -7 Torr.

[0034] In the technical solution of the present invention, the molecular line intensity of Cr atoms is 4x10 -8 ~5x10 -8 Torr;

[0035] Furthermore, the molecular line intensity of Cr atoms is 5x10 -8 Torr.

[0036] In the technical solution of the present invention, the doping concentration of iodine atoms is 10 20 ~1019 cm -3 ; N atom doping is done by ion implantation, and the N atom doping concentration is 10 19 ~10 18 cm -3 , the ratio of nitrogen atoms to iodine atoms is 1:8~10.

[0037] In the present invention, the CdI2 compound is heated to 120°C to 240°C, and I atoms begin to separate from the CdI2 compound, thereby being doped into the film as donor impurities. The doping concentration of I atoms increases as the heating temperature of CdI2 increases.

[0038] In the technical solution of the present invention, the CdI2 heating temperature is preferably 240°C. At this temperature, the iodine atom doping concentration is 10 19 cm -3 .

[0039] The reason for doping iodine in the present invention is that the (Zn, Cr)Te material itself is a semiconductor material, and carriers cannot move freely in the material, so it is necessary to dope (Zn, Cr)Te to obtain an n-type (Zn, Cr)Te semiconductor.

[0040] In the technical solution of the present invention, the N atom doping concentration is 10 18 cm -3 .

[0041] The purpose of nitrogen doping in the present invention is to change the state of 3d orbital electrons of Cr, increase the binding energy between Cr and the nearest neighboring Cr atoms, reduce the probability of metastable decomposition of the thin film material, thereby reducing the probability of formation of CrTe hexagonal unit cells, reduce the degree of deterioration of ZnTe sphalerite structure, and maintain the semiconductor properties of the thin film.

[0042] In the technical solution of the present invention, the nitrogen-containing (Zn 90% ,Cr 10% )The growth rate of the Te:I thin film layer is 0.1nm / s.

[0043] In the technical solution of the present invention, the nitrogen-containing (Zn 90% ,Cr 10% )The growth temperature of the Te:I thin film layer is 270~330℃.

[0044] Furthermore, nitrogen (Zn 90% ,Cr 10% )The growth temperature of the Te:I thin film layer is 300℃.

[0045] In the technical solution of the present invention, the nitrogen-containing (Zn 90% ,Cr 10%) The thickness of the Te:I thin film layer is 50 to 400 nm;

[0046] Furthermore, nitrogen (Zn 90% ,Cr 10% )The thickness of the Te:I thin film layer is 360nm.

[0047] Step 5: Nitrogen (Zn 90% ,Cr 10% ) Low temperature annealing treatment of Te:I thin film materials

[0048] The grown film is subjected to low temperature annealing treatment. This method can further increase the binding energy between Cr atoms, thereby improving the Cr atoms in nitrogen (Zn 90% ,Cr 10% )Te:I thin film is more evenly distributed.

[0049] In the technical solution of the present invention, the annealing temperature is 300-400° C. and the heat preservation time is 8-12 minutes.

[0050] Furthermore, in a specific embodiment of the present invention, the annealing temperature is 400° C. and the holding time is 10 min.

[0051] Another object of the present invention is to provide a nitrogen-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:I thin film material, wherein the concentration ratio of nitrogen atoms to iodine atoms per unit volume in the material is 1:8-10;

[0052] Furthermore, the electron concentration of the thin film material is 5×10 18 ~5×10 19 cm -3 , the resistivity is 5x10 2 ~5x10 3 Ωm

[0053] Furthermore, the electron concentration of the thin film material is 1×10 19 cm -3 , the resistivity is 1x10 3 Ωm.

[0054] The beneficial effects of the present invention are:

[0055] 1. The present invention uses N atom doping, which is beneficial to increase the binding energy between Cr atoms. Under the action of repulsive force, Cr atoms reduce the probability of forming CrTe hexagonal unit cells, thereby reducing the probability of metastable decomposition of Cr atoms in ZnTe crystals, so that Cr atoms are evenly distributed in ZnTe crystals, do not show metallic properties, and maintain the semiconductor properties of the material itself.

[0056] 2. I is an n-type semiconductor doping element, and N is a p-type semiconductor doping element. The present invention controls the type and concentration of carriers in the thin film material by co-doping I atoms and N atoms, and provides a new method for introducing carriers into a semiconductor (Zn, Cr)Te thin film material.

[0057] 3. The nitrogen-containing (Zn 90% ,Cr 10% )The ferromagnetic Curie temperature of Te:I is as high as 300K at room temperature, while the semiconductor properties of the material itself are also maintained, which has good prospects for industrial application.

[0058] 4. The present invention uses molecular beam epitaxy technology, and the growth of crystals can be carried out at low temperatures, which can achieve atomic-level film growth with a growth rate of 0.1 nm / s, which can maximize the crystal quality of the film.

[0059] 5. With undoped nitrogen (Zn 90% ,Cr 10% )Te:I thin film material, the X-ray intensity of the nitrogen-containing (Zn90%, Cr10%)Te:I thin film obtained by the present invention is increased by 3.9 times, and the half-amplitude is reduced by 0.12°, indicating that the existence ratio of CrTe hexagonal unit cells in the nitrogen-containing (Zn90%, Cr10%)Te:I thin film obtained by the present invention is reduced, and the ratio of sphalerite structure is increased, so the semiconductor properties of the material itself can be improved and the growth quality of the thin film can be enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 Based on the MBE method, Zn 90% ,Cr 10% ) Schematic diagram of Te:I thin film, in the figure, 1 represents the growth chamber of MBE, 2 represents the Te atomic source, 3 represents the Cr atomic source, 4 represents the N atomic source, 5 represents the Zn atomic source, 6 represents the CdI2 evaporation source, and 7 represents the film growth position, which is located in the center of the growth chamber.

[0061] Figure 2 This is a schematic side cross-sectional view of a semi-insulating GaAs substrate.

[0062] Figure 3 is a schematic side cross-sectional view of growing a ZnTe buffer layer on a GaAs substrate, where 1 indicates that the thickness of the ZnTe buffer layer is 360 nm;

[0063] Figure 4 In order to grow nitrogen-containing (Zn 90% ,Cr 10% )Te:I thin film layer side cross-sectional diagram, in which 1 represents nitrogen (Zn 90% ,Cr10% )The thickness of the Te:I thin film layer is 360nm.

[0064] Figure 5 The nitrogen-containing (Zn) 90% ,Cr 10% )Ferromagnetic property curve of Te:I thin film material.

[0065] Figure 6 The nitrogen-containing (Zn) 90% ,Cr 10% )Arrot Plot fitting curve of Te:I thin film material at different temperatures.

[0066] Figure 7 This is the RHEED image of the GaAs surface.

[0067] Figure 8 RHEED images of ZnTe buffer layer films of different thicknesses grown on treated GaAs substrates.

[0068] Fig. 9 RHEED images of ZnTe buffer layer films at different growth temperatures.

[0069] Fig.10 The nitrogen content (Zn 90% ,Cr 10% ) RHEED image of Te:I thin film material.

[0070] Fig.11 The nitrogen content (Zn 90% ,Cr 10% ) RHEED image of Te:I thin film material.

[0071] Fig.12 For nitrogen-free (Zn 90% ,Cr 10% ) X-ray refraction curve of Te:I film.

[0072] Fig.13 The nitrogen-containing (Zn 90% ,Cr 10% )X-ray reflection curve diagram of Te:I thin film material. DETAILED DESCRIPTION

[0073] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0074] Any feature disclosed in this specification (including any additional claims, abstract and drawings), unless otherwise stated, may be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0075] In the present invention, RHEED is an abbreviation for reflected high-speed electron back-electron eddy current. RHEED is usually used to track the crystal state of the film growth during molecular beam epitaxy. When the RHEED image reflects the arrangement of atoms within a few nm on the film surface, when the image is in the form of bands / dots and lines, it indicates that the film surface is in a single crystal state. When the image is in the form of rings, dots, or even no image, it indicates that the film surface is in a polycrystalline state or is uneven, and the crystal quality is very low.

[0076] Example 1

[0077] Step 1: Pre-growth treatment of the semi-insulating GaAs substrate

[0078] The present invention uses a volume ratio of desulfurized water: ionized water: hydrogen peroxide = 4:1:1 to soak and clean the GaAs substrate, stirring it at the same time, and the soaking and stirring cleaning time is 5 minutes. Finally, 99% anhydrous alcohol is used for cleaning and dehydration.

[0079] Step 2: Use molecular beam epitaxy to grow GaAs( Figure 2 ) Surface defects are treated

[0080] The specific method is to heat the GaAs substrate to 560°C and keep it for 5 minutes. Under this condition, the oxide can be completely removed. However, during the heating process of the GaAs substrate, especially when the temperature exceeds 400°C, As atoms will evaporate from the surface, causing lattice defects on the substrate surface, and it is necessary to compensate for the As atoms. The specific method of the present invention uses a Te atomic source to compensate for the As atoms, such as Figure 1 As shown, the Te atom source is heated to control the vacuum vapor pressure (molecular line intensity) of Te atoms to 5x10 -8 Torr.

[0081] Step 3: Growth of ZnTe buffer layer (Buffer) Figure 3 )

[0082] The lattice constant mismatch rate of GaAs and (Zn, Cr)Te:I reaches 7%, so it is necessary to grow a ZnTe buffer layer. The specific method is to set the substrate temperature to 300℃, heat the Zn atomic source and the Te atomic source so that the vapor pressure intensity ratio of Te / Zn reaches 1.5:1, and the vapor pressure intensity is 6x10 -8 Torr and 4x10 -8Torr. Under this condition, the growth rate of compound crystal is 0.1nm / s. After 1 hour of crystal growth, the lattice constant of ZnTe can reach The lattice constant is close to that of the (Zn, Cr)Te:I film, thereby ensuring the high-quality growth of the (Zn, Cr)Te:I film on the ZnTe layer.

[0083] Step 4: Nitrogen (Zn 90% ,Cr 10% )Te:I thin film growth ( Figure 4 )

[0084] The Zn, Cr and Te sources are heated to make the molecular line intensity ratio of Zn / Te reach 1.5:1 and the total molecular line intensity of Zn and Te atoms is 8x -7 Torr, 4.8x -7 Torr and 3.2x -7 Torr, the molecular line intensity of Cr is 5x10 -8 Torr, the heating temperature of CdI2 is 240℃. N atom doping is carried out by ion implantation, the discharge frequency is 13.56MHz, the discharge power is 300W, and the N2 flow rate is controlled at 0.1CC / min. 90% ,Cr 10% )The growth temperature of Te:I film is 300°C and the growth time is 1 hour. During the film growth process, the substrate needs to be rotated at a speed of 18° / second.

[0085] Step 5: Nitrogen (Zn 90% ,Cr 10% ) Low temperature annealing treatment of Te:I thin film materials

[0086] Treatment conditions: The film temperature is raised to 400°C and maintained for 10 minutes. This method can further improve the Cr atom in nitrogen-containing (Zn 90% ,Cr 10% )Te:I thin film, making the distribution more uniform.

[0087] Depend on Figure 5 As shown in the figure, at temperatures of 2K and 10K, the magnetic properties of the film show a typical "S"-shaped ferromagnetic characteristic curve as the applied magnetic field changes. At 300K, the "S"-shaped ferromagnetic characteristic curve shrinks, indicating that the ferromagnetic properties weaken at this temperature. Figure 6 The Arrot Plott calculation analysis results shown show that the film still retains ferromagnetic properties at a temperature of 300K, and the estimated value of the Curie temperature is 300K.

[0088] RHEED images of ZnTe buffer films of different thicknesses grown on treated GaAs substrates are shown in Figure 2. Figure 8 As shown. The fixed growth temperature is 300°C. When the film thickness is 50nm, there are both dot-line images. When the film thickness is 360nm, the linear pattern is most obvious, and when the thickness is 400nm, the image shows a dot-line trend. The optimal thickness of the ZnTe buffer layer of the present invention is 360nm.

[0089] The nitrogen-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:I thin film material. The Hall test results show that the carriers of the film are electrons, and the electron concentration can reach 10 19 cm -3 , nitrogen-containing semiconductors (Zn 90% ,Cr 10% )The resistivity of Te:I thin film can reach 1x10 3 Ωm, and the ferromagnetic Curie temperature of the film can reach 300K, while the film retains the properties of a semiconductor.

[0090] Test method: When the carriers in the semiconductor thin film material move in an external magnetic field, the movement trajectory is deflected due to the influence of the Lorentz force, and a potential difference is generated at both ends of the material. In this way, it can be concluded whether the carriers in the material are holes or electrons, and the resistivity and concentration of the carriers can be obtained by calculation. It has a wide range of applications in the field of semiconductor material research.

[0091] Test equipment: British OXFORD brand.

[0092] Example 2

[0093] RHEED images of ZnTe buffer layer films at different growth temperatures are shown in Figure 2. Fig. 9 As shown. The fixed film thickness is 360nm. It can be seen from the figure that when the growth temperature is 280℃, it basically presents a linear pattern, and the dot pattern is not obvious. When the growth temperature is 300℃, a very clear linear pattern is presented. When the growth temperature is 320℃, it basically presents a linear pattern, and there are also dot patterns. Therefore, the optimal growth temperature of the ZnTe buffer layer proposed by the present invention is 300℃.

[0094] Example 3

[0095] Fig.10 The nitrogen content (Zn 90% ,Cr 10%) RHEED image of Te:I film. The thickness of the film is 360nm. Under the growth temperature of 270℃, the RHEED image of the film shows a weaker dot-line arrangement. The dot-line arrangement is best at 300℃, and the RHEED dot-line arrangement is weakened at a growth temperature of 330℃. It can be shown that the growth temperature range suitable for the film is 270~330℃, and the optimal growth temperature is 300℃.

[0096] Example 4

[0097] Fig.11 The nitrogen content (Zn 90% ,Cr 10% ) RHEED image of Te:I film, the growth temperature of the film is 300℃. When the thickness of the film increases to 50nm, it shows a weaker dot-line pattern. As the thickness increases, the dot-line pattern becomes more obvious, and at 360nm, the dot-line pattern is the strongest, which means that at this thickness, the atoms on the surface of the film are arranged most neatly. When the thickness increases to 720nm, basically no obvious dot-line pattern is observed, which means that the atomic arrangement on the surface of the film is the worst at this time. The above RHEED images show that the suitable thickness range of the film is 50-720nm, and the optimal thickness is 360nm.

[0098] Comparative Example 1

[0099] like Figure 7 The image shown is a RHEED image of defects on the GaAs surface treated using molecular beam epitaxy. The left image is an image without using Te atoms to compensate As atoms. The image shows a dotted pattern, which means that As atoms detach from the GaAs substrate after exceeding 400°C, and Ga atoms remain on the surface, resulting in an uneven surface of the substrate. The right image is an image after compensation using Te atoms. The image shows a linear pattern, which indicates that Te atoms combine with the remaining Ga atoms to fill the vacancies left by the As atoms, thereby improving the flatness of the GaAs substrate surface to avoid unevenness in the ZnTe buffer layer grown on it, thereby improving the crystallization quality of the multilayer film.

[0100] Comparative Example 2

[0101] Fig.12 For nitrogen-free (Zn 90% ,Cr 10% )Te:I thin film X-ray refraction curve diagram, through the X-ray refraction curve, in the range of 60 ° ~ 62 ° there are nitrogen (Zn 90% ,Cr 10%)The inflection peak of the (004) plane of the Te:I film has a peak value of 60.66° and an intensity of 3800, which is close to the inflection peak angle of 60.653° (theoretical value) of the (004) plane of the ZnTe semiconductor, and the half-width is 0.79°. Fig.13 The nitrogen-containing (Zn 90% ,Cr 10% )Te:I thin film X-ray refraction curve diagram, in the range of 60 ° ~ 62 ° there are nitrogen (Zn 90% ,Cr 10% )The inflection peak of the (004) plane of the Te:I film has a peak value of 60.66° and an intensity of 15000, which is close to the inflection peak angle of 60.653° (theoretical value) of the (004) plane of the ZnTe semiconductor, and the half-width is 0.67°.

[0102] By comparison Fig.12 and Fig.13 , using the nitrogen-containing (Zn 90% ,Cr 10% )Te:I film X-ray intensity increased by 3.9 times, and half amplitude decreased by 0.12°, which can be explained by the use of the present invention to obtain nitrogen-containing (Zn 90% ,Cr 10% )The existence ratio of CrTe hexagonal unit cells in the Te:I film decreases, and the proportion of the blende structure increases, thereby improving the semiconductor properties of the material itself and enhancing the growth quality of the film.

[0103] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation methods of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A nitrogen-containing diluted magnetic semiconductor (Zn 90% , Cr 10% ) A method for preparing a Te:I thin film material, comprising the following contents: The semi-insulating GaAs substrate was treated before growth: the GaAs substrate was soaked and cleaned with desulfurized water: ionized water: hydrogen peroxide in a volume ratio of 4:1:1, and then cleaned and dehydrated with 99% anhydrous alcohol; Use molecular beam epitaxy technology to treat GaAs surface defects: heat the GaAs substrate to 560°C and keep it for 5 minutes to remove the oxide, and then treat the GaAs surface defects; when using molecular epitaxy technology to treat GaAs substrate surface defects: the atoms used when using molecular epitaxy technology to treat GaAs substrate surface defects are one or more of As atoms, Te atoms, and Se atoms; Growth of ZnTe buffer layer: The growth of ZnTe buffer layer refers to the growth of ZnTe buffer layer on GaAs substrate using molecular beam epitaxy technology; wherein the molecular line intensity ratio of Zn / Te is 1:1.5, the growth temperature of ZnTe buffer layer is 280~320℃, and the thickness of buffer layer is 50~400 nm; Nitrogen (Zn 90% , Cr 10% ) Growth of Te:I thin film layer: Heat the Zn atomic source, Cr atomic source and Te atomic source to make the molecular line intensity ratio of Zn / Te reach 1.5:1, and the total molecular line intensity of Zn atoms and Te atoms is 4.8x10 -7 Torr and 3.2x10 -7 Torr, the molecular line intensity of Cr is 5x10 -8 Torr, the heating temperature of CdI2 is 240℃; N atom doping is carried out by ion implantation, the discharge frequency is 13.56MHz, the discharge power is 300W, and the N2 flow rate is controlled at 0.1CC / min; nitrogen (Zn 90% ,Cr 10% ) The growth temperature of Te:I film is 300°C, the growth time is 1 hour, and the substrate needs to be rotated during the film growth process at a speed of 18° / s; Growth nitrogen (Zn 90% , Cr 10% ) Low temperature annealing treatment of Te:I thin film material, the film temperature is raised to 400℃ and maintained for 10 minutes.

2. The preparation method according to claim 1, characterized in that: The growth temperature of the ZnTe buffer layer is 300°C.

3. The preparation method according to claim 1, characterized in that: The growth thickness of the ZnTe buffer layer is 50~360nm.

4. The preparation method according to claim 3, characterized in that: The growth thickness of the ZnTe buffer layer is 360nm.

5. The preparation method according to claim 1, characterized in that: Nitrogen (Zn 90% , Cr 10% ) Growth of Te:I thin film layer: The doping concentration of iodine atoms is 10 19 cm -3 ; N atom doping concentration is 10 18 cm -3 , the ratio of nitrogen atoms to iodine atoms is 1:

10.

6. The preparation method according to claim 1 or 5, characterized in that: Nitrogen (Zn 90% , Cr 10% )The thickness of the Te:I thin film layer is 100~720 nm, and the growth rate is 0.1nm / s.

7. The preparation method according to claim 6, characterized in that: Nitrogen (Zn 90% , Cr 10% )The thickness of Te:I thin film layer is 50~400nm.

8. The preparation method according to claim 7, characterized in that: Nitrogen (Zn 90% , Cr 10% )The thickness of the Te:I thin film layer is 360nm.

9. The preparation method according to claim 1, characterized in that: The atoms used to treat the surface defects of GaAs substrates using molecular epitaxy technology are Te atoms.

10. The preparation method according to claim 9, characterized in that: The molecular line strength of Te atoms is 5x10 -8 Torr.

11. A nitrogen-containing diluted magnetic semiconductor (Zn 90% , Cr 10% )Te:I thin film material, prepared by the preparation method according to any one of claims 1 to 10, characterized in that: The concentration ratio of nitrogen atoms to iodine atoms per unit volume in the material is 1:8~10, and the electron concentration of the thin film material is 5×10 18 ~5×10 19 cm -3 , the resistivity is 5x10 2 ~5x10 3 Ωm.

12. The thin film material according to claim 11, characterized in that: The concentration ratio is 1:10, and the electron concentration of the thin film material is 1×10 19 cm -3 , the resistivity is 1x10 3 Ωm.

Citation Information

Patent Citations

  • Highly-doped ZnO:Co magnetic semiconductor film material and preparation method thereof

    CN103400679A